The Northernmost Ruins of the Globe (Vol. 329):Eigil Knuth's Archaeological Investigations in Peary Land and Adjacent Areas of High Arctic Greenland - Grønnow, Bjarne (Monographs on Greenland | Meddelelser om Grønland, 2003)
An important part of the heritage of Count Eigil Knuth (1903-1996) is his archaeological archive including contextual information on prehistoric sites gathered during six decades of research in High Arctic Greenland. The finds and observations are a key to the understanding of human life under extreme conditions in a long-term perspective and represent a unique piece of evidence concerning the early cultural history of the Eastern Arctic. Knuth's expeditions from 1932 to 1995 took him to Greenland and Canada, in particular High Arctic Greenland. In a number of important articles Knuth published the findings dating back to the earliest human settlement in Greenland. However, he never managed to present the complete body of information and results from his many investigations. The present authors have thus compiled a computer data base based on his archive, and this has formed the starting point of the present book. The book focuses on Knuth's most substantial contribution to archaeology: the prehistory of Peary Land and adjacent areas. In the catalogue emphasis has been placed on topographical and architectural information, site structure, artefact statistics and radiocarbon dates. A total of 154 archaeological sites are presented. 51 sites with a total of 244 features are Independence I sites (c. 2460 - 1860 cal. BC), 23 sites with a total of 416 features belong to Independence II (c. 900 - 400 cal. BC) and 63 sites with a total of 626 features are of Thule origin (c. 1400 - 1500 ca. AD). It has not been our ambition to re-analyse the finds or add new empirical data in connection with the production of this book. We do, however, present some new information on the faunal material from Peary Land based on Christyann Darwent's recent analyses as well as new data on the dwelling features on the Adam C. Knuth Site, which was visited by a multidisciplinary team in 2001. The book is provided with an introduction presenting an overview and evaluation of Knuth's remarkable curriculum vitae as an independent arctic archaeologist. In the concluding chapters some basic statistics on the archaeological sites are presented. We evaluate Knuth's radiocarbon datings of the Independence I, Independence II and Thule cultures in High Arctic Greenland, and settlement distributions and settlement patterns for the three cultures represented in Peary Land are discussed.